Systemic process of “on-time delivery” in aerospace composites manufacturing company - Rozita, Long (2018)
There is a lack of systemic resource deployment strategy in producing the right, acceptable quality of wing panel, in the right quantity, complete and delivered on time. Thus, a study was done to examine the systemic impact of the number of labour, output, output accuracy and work-in-process on on-time delivery and net sales from a resourcebasedview perspective. The resource-based view theory was the underpinning theory in this study used to explain the implication of resource and capability utilization in an organization. Together with the theory of labour to explain the significance of labour as value creator, the theory of constraints explains the significance of a drum buffer rope concept to create an invisible link that tie up work- in-process at the shop floor and at the same timeidentify the bottleneck in the manufacturing flow to produce theright panel, in the right quantity at the right time. A multivariate statistical analysis tool was applied through a formative-causal relation type of study using a correlational approach. The study revealed that labour has the most significant impact on on-timedelivery compared to output, output accuracy or work-in-process.Research contribution to the theory, organization, industry and academic is truly evident. A documented real objective research concerning aerospace industry hasadded another value to the corpus of knowledge in resource-based view theory, theory of labour and theory of constraint. The research findings created another optionalstrategy for resource and capabilities management in the aerospace manufacturing industry. The study provided a platform for the academic practioners to test their knowledge in a real situational business case. The limitation of this study could inadvertently prove to be an opportunity for further research. Even though the study found that labour was the major contributor to on-time delivery, it did not address how to manage or how to fully utilize labour as the most important resource in the manufacturing sector. This could be another potential area for future research.